Novel recurrent chromosome anomalies in Shwachman–Diamond syndrome. Issue 8 (28th January 2017) - Valli, Roberto; De Paoli, Elena; Nacci, Lucia; Frattini, Annalisa; Pasquali, Francesco; Maserati, Emanuela
Abstract: Background: Two chromosome anomalies are frequent in the bone marrow (BM) of patients with Shwachman–Diamond syndrome (SDS): an isochromosome of the long arm of chromosome 7, i(7)(q10), and an interstitial deletion of the long arm of chromosome 20, del(20)(q). These anomalies are associated with a lower risk of developing myelodysplasia (MDS) and/or acute myeloid leukemia. The chromosome anomalies may be due to an SDS‐specific karyotype instability, reflected also by anomalies that are not clonal, but found in single cells in the BM or in peripheral blood (PB). Procedure: Starting in 1999, we have monitored the cytogenetic picture of a cohort of 91 Italian patients with SDS by all suitable cytogenetic and molecular methods. Results: Here, we report clonal chromosome anomalies that are different from the aforementioned, as well as changes found in single cells in BM/PB of the same patients. Conclusions: Some of the newly recognized clonal anomalies in BM reported here are recurrent, especially unbalanced structural anomalies of chromosome 7, a further complex rearrangement of the del(20)(q) with duplicated and deleted portions, and an unbalanced translocation t(3;6), with partial trisomy of the long arm of chromosome 3 and partial monosomy of the long arm of chromosome 6. Firm conclusions on the possible prognostic relevance of these anomalies would require further study with larger patient cohorts, but our data are sufficient to suggest that these patients necessitate more frequent cytogenetic monitoring. The results on anomalies found in single cells confirm the presence of an SDS‐specific karyotype instability.